Pengembangan Buku Panduan Kontekstual Berbasis Buku Cerita untuk Penguatan Literasi Budaya Anak Usia 5–6 Tahun - Fitriyani, Fitriyani; Sukiman, Sukiman; Puridawaty, Brigita (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
Cultural literacy in early childhood is important for shaping identity and fostering an appreciative attitude towards diversity from an early age. This study aims to develop a contextual guidebook based on storybooks to strengthen cultural literacy for children aged 5–6 years and assess its feasibility and implementation in early childhood education. The study used a Research and Development (R&D) method with the 4D model (define, design, develop, disseminate). The dissemination stage was carried out through a limited trial, focusing on the product's feasibility and implementation, rather than broad effectiveness testing. Data were collected through observations, interviews, validation by content, language, and media experts, and a limited trial. Data were analyzed descriptively and quantitatively (percentage and N-gain) to assess the product's feasibility and the changes in children's cultural literacy achievements before and after using the guidebook. The results showed that the guidebook was deemed feasible based on expert evaluation, and the limited trial indicated an improvement in cultural literacy, particularly in children’s interest in cultural stories, involvement in storytelling activities, comprehension of story content, and emotional responses during learning. These findings suggest that the guidebook is practical for use by PAUD teachers and supports the development of instructional materials based on local cultural stories.